Pseudomonas aeruginosa utilizes host polyunsaturated phosphatidylethanolamines to trigger theft-ferroptosis in bronchial epithelium - Dar, Haider H. (J Clin Invest, 2018)
Ferroptosis is a death program executed via selective oxidation of arachidonic acid–phosphatidylethanolamines (AA-PE) by 15-lipoxygenases. In mammalian cells and tissues, ferroptosis has been pathogenically associated with brain, kidney, and liver injury/diseases. We discovered that a prokaryotic bacterium, Pseudomonas aeruginosa, that does not contain AA-PE can express lipoxygenase (pLoxA), oxidize host AA-PE to 15-hydroperoxy-AA-PE (15-HOO-AA-PE), and trigger ferroptosis in human bronchial epithelial cells. Induction of ferroptosis by clinical P. aeruginosa isolates from patients with persistent lower respiratory tract infections was dependent on the level and enzymatic activity of pLoxA. Redox phospholipidomics revealed elevated levels of oxidized AA-PE in airway tissues from patients with cystic fibrosis (CF) but not with emphysema or CF without P. aeruginosa. We believe that the evolutionarily conserved mechanism of pLoxA-driven ferroptosis may represent a potential therapeutic target against P. aeruginosa–associated diseases such as CF and persistent lower respiratory tract infections.